SAT0353 Association of Gouty Arthritis Severity with Patients' Mental and Physical Health-Related Quality of Life, Work Productivity and Medical Resource Utilization. (23rd January 2014) - Schlesinger, N.; Radvanski, D.; Tomanovich, P.
Abstract : Background: Painful flares and underlying inflammation in gouty arthritis (GA) diminishes patients' health-related quality of life (HRQoL); particularly in those experiencing frequent flares. Few studies have assessed HRQoL, work productivity and medical resource use according to GA severity. Objectives: We hypothesize that GA severity is associated with decreased HRQoL and productivity, and greater medical resource utilization. Methods: In a cross-sectional study, GA patients participating in a US chronic illness panel; who met eligibility (men and women ≥18, with ≥ 1 flare within the last 12 months) completed an online IRB-approved survey, evaluating demographics, HRQoL (SF-36), activities of daily living, work productivity (WPAI), and medical resource use. Respondents were grouped according to disease severity (number of flares within last 12 months): Low: 1-3 flares; Moderate: 4-5 flares; High: ≥ 6 flares. ANOVA between groups applied to dependent variables. A regression analysis controlled for confounding covariates. Covariates: age, gender, employment, co-morbidities, and severity. Results: 6, 469 invited respondents; 2, 031 (33%) responded; 599 (9%) found eligible completed the survey within 10 days of enrollment. 500 (84%) males. Mean age: 54.6 (±12.6) yrs; mean disease duration: 11.5 (±10.4) yrs. Disease severity groups: Low n=321; Moderate: n=205; High n=73. Significantly more flares per year in younger vs. older respondents (p= 0.027). Mean flare duration: 4.5 (±4.7) days. 27% on urate-lowering therapy (ULT); 27% on chronic colchicine; 8% on both. No difference between groups. High Severity vs. Mild and Moderate respondents had significantly lower SF-36 Physical Component scores (Mild: p<0.01; Moderate: p=0.04) and significantly lower scores vs. Mild respondents on the SF-36 Physical Functioning (Mild: p<0.01), Role-Physical (p<0.01), Bodily Pain (p<0.01), General Health (p<0.01), Vitality (p=0.01), and Social Functioning (p<0.01) Total respondents: 3% work time missed; 16% impairment while working; 17% overall work impairment; and 20% activity impairment due to gout. High Severity vs. Mild and Moderate respondents had significantly higher WPAI scores on % impairment while working (p<0.001; p<0.01); % overall work impairment (p<0.01 and p<0.01); % impairment (p<0.01; p<0.01); significantly higher vs. Mild respondents % work time missed (p<0.01). High Severity vs. Mild and Moderate respondents had significantly higher utilization of after-hours urgent care visits post flare (p<0.01; p<0.01); significantly higher vs. Mild respondents doctor visits (p<0.01), prescriptions (p<0.01), and emergency room visits (p<0.01). Conclusions: In this large internet survey study evaluating HRQoL and work productivity in GA patients, severe GA patients experience significantly lower work productivity, and HRQoL and utilize significantly more medical resources compared to patients who have lower burden of disease. Further studies are needed to better understand the health burden in severe GA patients References: Funding for this research was provided by Novartis Pharmaceuticals Corporation. Disclosure of Interest: N. Schlesinger Grant/research support from: Novartis, Consultant for: Novartis, Sobi, Speakers bureau: Savient, Takeda, Novartis, D. Radvanski: None Declared, P. Tomanovich: None Declared